Food behaviours and eating habits among Sub-Saharan African migrant mothers of school-aged children in South Australia - William Mude; Tafadzwa Nyanhanda (Journal of Migration and Health, 2023)
Abstracts: Overweight, obesity and chronic conditions like diabetes, stroke and heart disease represent a significant burden to public health. Traditional foods and healthy dietary habits can reduce the risk of these conditions. Therefore, this study aimed to explore traditional food patterns and eating habits among Sub-Saharan African migrant mothers of school-aged children in South Australia. The study was a qualitative inquiry that used face-to-face interviews with 15 mothers of school-aged children in South Australia. Snowballing was used to sample participants, and data were audio-recorded, transcribed verbatim, coded, and analysed thematically. Four broad themes described participants’ food behaviours and eating habits, including maintaining traditional food patterns, changes in traditional food patterns and eating habits, concerns with food environments in Australia, and challenges with traditional food availability and access in Australia. This study found that although mothers were committed to maintaining their traditional foods, they found it increasingly difficult to continue such habits. Participants reported challenges as their children are increasingly demanding westernised foods. While some parents pushed back against such demands from their children, others felt helpless and relented. Some views showed that food environments, food systems, access, and scarcity of traditional foods in Australia influenced the participants’ food patterns and eating habits. Appropriately tailored healthy eating health promotion actions targeting school-aged children and mothers in this population need to consider their food contexts. Promoting the use of traditional foods, their preparation practices, and processing might be helpful in this community when developing healthy eating programs.